2021
DOI: 10.1186/s12903-021-01911-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and beliefs regarding molar incisor hypomineralisation amongst Swiss dental students

Abstract: Background Knowledge obtained at the undergraduate level regarding molar incisor hypomineralisation (MIH) has an impact on future practice of dentists and paediatric dentists. This cross-sectional study aimed to assess final-year dental students’ knowledge, attitudes and beliefs towards MIH in all Swiss universities. Methods A previously utilised survey (in both English and German) was distributed among final-year dental students in all Swiss denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 15 publications
9
18
0
4
Order By: Relevance
“…This conclusion is also supported by another finding where more than two thirds (75.2%) of the dental students in the present study reported knowing the diagnostic criteria of MIH without knowing how to implement them clinically. These findings agreed with those of similar studies where most dental students had knowledge about the clinical features of MIH [ 18 – 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This conclusion is also supported by another finding where more than two thirds (75.2%) of the dental students in the present study reported knowing the diagnostic criteria of MIH without knowing how to implement them clinically. These findings agreed with those of similar studies where most dental students had knowledge about the clinical features of MIH [ 18 – 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Results from this crosssectional study showed that nearly two thirds (69.2%) of the dental students were familiar with MIH and that the most common sources of information for them were lectures and lecture notes, followed by the internet and clinical supervisors in the dental clinic. These findings are consistent with similar studies [18][19][20][21], but in contrast with a study in Saudi Arabia where 64% of the dental students had not heard about it [17].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations